Optimal preparation method of spinning solution for producing acrylic fiber precursor of carbon fiber and related carbon fiber

The homogeneous spinning solution using DMSO and ammonia/amine mixtures uniformly treats PAN precursors, addressing inefficiencies and safety concerns in current methods, producing high-quality carbon fibers with improved mechanical properties.

JP7600484B2Active Publication Date: 2024-12-17MONTEFIBRE MAE TECH SRL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020139352
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-20
Filing Date
2020-08-20
Publication Date
2024-12-17
Estimated Expiration
2040-08-20

AI Technical Summary

Technical Problem

Current methods for producing carbon fibers from acrylic precursors (PAN) are inefficient, costly, and result in carbon fibers with unsatisfactory quality due to uneven heat treatment and the use of hazardous reagents like gaseous ammonia, which complicates the production process and increases energy consumption.

Method used

A method involving a homogeneous spinning solution prepared by mixing powdered acrylonitrile copolymer with DMSO and ammonia or primary/secondary amines in an aqueous solution, followed by heating to dissolve the polymer completely, ensuring all carboxyl groups are uniformly salified, thereby producing a high-quality precursor for carbon fibers.

Benefits of technology

This method reduces production costs and time, enhances the tenacity and modulus properties of carbon fibers, and eliminates the need for hazardous reagents, resulting in high-performance carbon fibers suitable for conventional manufacturing processes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an optimum preparing method of a spinning dope for manufacturing an acrylic fiber precursor (PAN) of carbon fiber.SOLUTION: There is provided a preparing method of a homogeneous spinning dope for manufacturing an acrylic precursor (PAN) of carbon fiber, in which the method comprises a step of i) mixing a powdery acrylonitrile copolymer with a solvent composed of a mixture containing DMSO in an amount ranging from 90 to 99 wt.% based on the total weight of the solvent, and an aqueous solution of ammonia and / or one or more kinds of primary amines and / or one or more kinds of secondary amines in an amount ranging from 1 to 10 wt.% based on the total weight of the solvent at a temperature of a range of 5 to 10°C, thereby preparing a homogeneous suspension.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optimal method for preparing a spinning solution for producing an acrylic fiber precursor (PAN) of carbon fiber, and an optimal method for producing carbon fiber from the acrylic precursor (PAN).

[0002] More specifically, the invention is in the field of carbon fiber production. Methods for the preparation of carbon fibers have been known for many years and are mostly based on the thermal treatment of suitable acrylic precursors (PAN) with a chemical composition suitable for the controlled, gradual removal of heteroatoms. [Background technology]

[0003] This gradual removal of heteroatoms is achieved by the presence of certain comonomers in the polymer chain of the precursor, which have groups capable of distributing the heat generated during the oxidation / flameproofing treatment over a relatively long period of time. This avoids a sharp exothermic peak, which not only results in a low-quality carbon fiber, but also exposes it to the risk of uncontrolled combustion during this heating stage. The most commonly used comonomers for this purpose are vinyl carboxylates or vinyl dicarboxylates. In particular, acrylic acid, methacrylic acid or itaconic acid are used in amounts usually ranging from 0.5 to 5% by weight, relative to the total weight of monomers fed to the polymerization reactor. The other reagents are mainly acrylonitrile (95 to 99.5% by weight) and, optionally, a third component (0 to 3.0% by weight), generally chosen from methyl acrylate, vinyl acetate and acrylamide.

[0004] PAN precursors can be prepared by a variety of methods starting with selected comonomers. The current technology can be organized into the following categories: A. Discontinuous method (2 steps)

[0005] In the two-step discontinuous process, the polymer is generally produced in aqueous suspension, isolated, dissolved in a suitable solvent, and spun into fibers to convert it into the fiber precursor for carbon fibers. The most commonly used solvents for the preparation of the spinning solution are dimethylacetamide (DMAC), dimethylformamide (DMF), and aqueous sodium thiocyanate (NaSCN). B. Continuous method (one step).

[0006] However, in continuous processes, polymerization takes place in a solvent and the solution thus obtained is used directly for spinning without intermediate polymer separation. The most commonly used solvents in these processes are dimethylformamide (DMF), dimethylsulfoxide (DMSO), aqueous zinc chloride (ZnCl2), and aqueous sodium thiocyanate (NaSCN).

[0007] These methods readily yield a wide variety of carbon fibers with standard properties of toughness and elastic constants, as is well known to those skilled in the art, although several modifications to these methods have been proposed to improve the performance of the resulting fibers.

[0008] One of the most significant changes concerns the use of nitrogen compounds in the process for producing PAN precursors, specifically the use of low molecular weight primary and secondary amines and, above all, ammonia.

[0009] Specifically, U.S. Patent No. 5,804,108, U.S. Patent No. 6,054,214, and U.S. Patent Application Publication No. 2009 / 0224420(A1) describe methods to increase the elastic modulus of produced carbon fibers by up to 2.5 times.

[0010] In this method, a PAN precursor containing itaconic acid is treated with an amine or ammonia during the spinning stage. Specifically, the PAN fibers are treated with a water bath containing an amine or ammonia immediately after the coagulation stage at the exit of the spinneret, and the fibers are treated at a temperature in the range of 240-260°C for 12-15 minutes before being carbonized after spinning is completed.

[0011] The reaction mechanism is believed to be that itaconic acid is salified with amines or ammonia. These ammonium salts are converted to amides after heat treatment, which then attack the nitrile groups in the polymer chains, causing crosslinking of the PAN fibers.

[0012] It is particularly important that this chlorination step with ammonia or amines occurs uniformly and affects all the polymers that make up the fiber, and not just the carboxyl groups on the outer surface of the fiber, which are more directly exposed to contact with the ammonia or amine dissolved in water. In the case of partial chlorination limited to the most superficial part of the fiber, the outer surface of the fiber in fact behaves differently to the heat treatment compared to the interior of the PAN precursor, resulting in carbon fibers of unsatisfactory quality. In order to ensure the necessary homogeneity in the chlorination of all the carboxyl groups, the treatment with ammonia or amines must be carried out under suitable drawing and relaxation conditions, which allow the ammonia or amine to penetrate also into the interior of the fiber structure.

[0013] Other patents, such as JP 11-12856(A), US 8,137,810, and US 8,674,045, claim the direct use (doping) of gaseous ammonia into the spinning solution. In these cases, the main motivation for using ammonia is the neutralization of the acid groups carried by the comonomers used (mainly itaconic acid and acrylic acid). The salification of the acid groups with ammonia to obtain ammonium carboxylates improves the process of production of PAN precursors and facilitates the coagulation stage due to the highly hydrophilic nature of the polymer chains after salification of the acid end groups and their conversion to ammonium salts.

[0014] This neutralization method ensures homogeneity of the process since the polymer is dissolved in the solvent and therefore there are no regions of different reactivity, as occurs conversely when working with heterogeneous phases with a solid (PAN fiber) immersed in an aqueous solution of ammonia or an amine.

[0015] Regardless of the mechanism involved, the use of ammonia or primary or secondary amines contributes to the production of higher quality carbon fibers than those obtained in the absence of ammonia or amines. A further advantage lies in the reduction of the heat treatment time required to reach a fiber density of at least 1.35-1.43 g / cc, which is necessary to feed the oxidized product (PANOX) to the carbonization furnace. This reduction in the flame retardation time brings considerable advantages both in terms of energy consumption and investment in building the flame retardation furnace.

[0016] In any event, the above methods necessarily provide an additional step in the preparation of the PAN precursor.

[0017] In US Patent Application 2009 / 0224420(A1) one step must be added to add amine or ammonia under stretching conditions, followed by a relaxation phase followed by a new stretching phase at higher temperature. US Patents 8,137,810 and 8,674,045 provide for the use of difficult and dangerous reagents such as gaseous ammonia, which is characterized as a toxic gas.

[0018] On the other hand, European Patent No. 2,894,243 (U.S. Patent No. 9,296,889) describes a method for preparing acrylic fibers, i.e., carbon fiber precursors, in which an acrylic polymer containing itanic acid or acrylic acid is dissolved under certain conditions, specifically, a DMSO / water mixture with a ratio ranging from 94.5 / 5.5 to 97 / 3 by weight. Summary of the Invention [Problem to be solved by the invention]

[0019] The object of the present invention is therefore to provide an optimal method for preparing a spinning solution for the production of acrylic fiber precursors (PAN) of carbon fibers, in particular an optimal method for the production of carbon fibers from acrylic precursors (PAN), which overcomes the drawbacks of the current state of the art methods, reduces production costs and, in particular, makes it possible to obtain carbon fibers with particularly high tenacity and high modulus properties. [Means for solving the problem]

[0020] The present invention therefore relates to a method for the preparation of a homogeneous spinning solution for the production of acrylic precursors (PAN) of carbon fibers, the method comprising the steps of: i) preparing a homogeneous suspension by mixing the powdered acrylonitrile copolymer with a solvent consisting of a mixture containing DMSO in an amount ranging from 90 to 99% by weight and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 1 to 10% by weight, relative to the total weight of the solvent, at a temperature ranging from 5 to 10°C, preferably with a solvent consisting of a mixture containing DMSO in an amount ranging from 93 to 98% by weight, preferably 93 to 96% by weight, relative to the total weight of the solvent, and an aqueous solution of ammonia or primary amines or secondary amines in an amount ranging from 2 to 7% by weight, preferably 4 to 7% by weight, relative to the total weight of the solvent, at a temperature of 5°C, said mixing being carried out for a time ranging from 5 to 30 minutes by spraying a stream of DMSO solvent / ammonia or aqueous solution of primary amines or secondary amines into a stream of deagglomerated premixed acrylonitrile copolymer powder; ii) heating the homogenous suspension from step i) at a temperature ranging from 70 to 150° C. for a time ranging from 0.5 to 30 minutes until the copolymer is completely dissolved and a homogenous solution is formed; Includes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The aqueous solution of ammonia or a primary or secondary amine contains 1 to 10% by weight, preferably 2 to 7% by weight, of a nitrogen-containing compound based on the total weight of the solution.

[0022] The aqueous solution is preferably an aqueous solution of ammonia or a primary or secondary amine.

[0023] The solvent preferably consists of a mixture containing DMSO and aqueous ammonia.

[0024] In the aqueous solution of primary and / or secondary amines, the primary amine is selected from methylamine, ethylamine and isopropylamine, preferably methylamine, and / or the secondary amine is selected from dimethylamine, diethylamine and diisopropylamine, preferably dimethylamine.

[0025] The polymers used in the process object of the present invention are high molecular weight copolymers in the range of 100,000 to 300,000 Da, consisting essentially of acrylonitrile in an amount ranging from 90 to 99% by weight, relative to the total weight of the polymer, and one or more comonomers in an amount ranging from 1 to 10% by weight, relative to the total weight of the polymer.

[0026] Suitable comonomers are vinyl molecules having one or more acid groups, such as acrylic acid, methacrylic acid, itaconic acid, preferably itaconic acid. The copolymer may also optionally contain a third comonomer selected from neutral vinyl molecules such as methyl acrylate, methyl methacrylate, vinyl acetate, acrylamide, etc.

[0027] The homogeneous spinning solution obtained at the end of the process according to the invention is free of gels and undissolved residues and can be fed directly to a spinning line or storage tank.

[0028] The invention thus makes it possible to obtain a gel-free acrylonitrile copolymer solution without the formation of insoluble aggregates by reducing the solvent capacity of DMSO in the first contact step between the powdered polymer and the solvent. This results in the formation of a homogeneous suspension (slurry), which is then transformed into a homogeneous solution without gels and insoluble matter by heating the suspension itself. Thus, the method according to the invention makes it possible to easily integrate the two steps of polymerization and spinning.

[0029] A good quality spinning solution free of gels and insoluble materials is thus obtained by step i) of preparing a homogeneous slurry under insoluble conditions for the polymer and then step ii) of rapidly heating the slurry thus obtained. Insoluble conditions for the polymer in DMSO are achieved by adding water in an aqueous solution of ammonia or an amine to the DMSO.

[0030] The presence of water has the dual effect of lowering the freezing temperature of the solvent from 18°C ​​for pure DMSO to approximately 0-7°C, depending on the water content, and also significantly reducing the solubilizing properties of the resulting mixture compared to pure DMSO.

[0031] The main advantage of the method for preparing PAN precursor according to the invention is that it allows the preparation of a homogeneous suspension of the polymer in an aqueous DMSO solvent. Under these conditions, the solvent can actually penetrate into the interior of each polymer particle, without partial dissolution resulting in the formation of a dope surface coating that prevents homogeneous wetting of all the polymeric material.

[0032] By rapid heating of the suspension homogeneously impregnated with the solvent, a very high quality dope is obtained, which is suitable for the preparation of high quality and high performance carbon fibers by conventional manufacturing techniques.

[0033] The method according to the invention represents an optimal solution for the homogeneous introduction of ammonium groups at the carboxyl end groups of the acid comonomers, by allowing and even supporting an intimate contact between the solvent and every single polymer particle. This homogeneous salification is particularly simple and efficient, due to the use of aqueous solutions of ammonia or amines as co-solvents in DMSO, which subsequently makes it possible to obtain high quality and high performance carbon fibers.

[0034] During the preparation of the slurry, under non-dissolving conditions, the ammonia or amine contained in the solvent used (a mixture of DMSO and an aqueous solution of ammonia or a primary or secondary amine) comes into intimate contact with all the carboxyl groups of the polymer by conditions of uniform and complete infiltration of the polymer powder according to the invention.

[0035] By rapid heating of the slurry thus prepared, a spinning dope is obtained in which all acid groups are salified with ammonia or primary or secondary amines, a condition comparable to that obtained by diffusion of gaseous ammonia in the dope, as described, for example, in US Patents 8,137,810 and 8,674,045.

[0036] The advantageous and simplified aspects of the dope preparation method according to the present invention are clear. Firstly, neutralized dope is obtained by using harmless dilute aqueous solution of ammonia or amine without any modification of existing preparation method. On the other hand, on the other hand, it has the disadvantage of being a dangerous and toxic reagent, and the use of gaseous ammonia also requires a processing step and specific equipment for this purpose.

[0037] The present invention also relates to a method for producing carbon fibers, which comprises subjecting the homogeneous solution obtained above to the following further steps: iii) spinning the homogeneous solution resulting from step ii) to obtain a tow containing 500 (0.5K) to 400,000 (400K) single fibers, preferably 1,000 (1K) to 50,000 (50K) single fibers. iv) feeding the tow resulting from step iii) to a flameproofing or oxidation step, where oxidation is carried out at a temperature in the range of 240-260° C. for a time in the range of 40-120 minutes. v) feeding the oxidized tow resulting from step iv) to a carbonization step at a maximum temperature of 1,600°C.

[0038] The invention further relates to a homogeneous spinning solution for the production of acrylic fiber precursors of carbon fibers and to carbon fibers obtainable by the method according to the invention.

[0039] The flameproofing process, also called oxidation, provides for the treatment of the PAN precursor in the form of a tow containing various amounts of filaments depending on the type of carbon fiber desired. Tows containing 500 (0.5K) to 400,000 (400K) filaments can be used, preferably those containing 1,000 (1K) to 50,000 (50K) filaments. The tows coming out of the spinning machine are collected on reels or in boxes or caissons from which they can be easily removed and fed to the flameproofing section.

[0040] A further advantage of the process according to the invention is that the acrylic precursor or PAN precursor thus obtained can be flameproofed faster and at lower temperatures in the flameproofing / oxidation step which precedes the final carbonization step in the production of carbon fibers. EXAMPLES

[0041] As non-limiting examples of the present invention, examples of some embodiments of the method according to the present invention and some comparative examples are given below. Example 1 (reference)

[0042] Dissolution of high molecular weight acrylic copolymers (nMW=150,000-180,000) consisting of acrylonitrile (96% by weight based on the total weight of the polymer), itaconic acid (1% by weight based on the total weight of the polymer) and methyl acrylate (3% by weight based on the total weight of the polymer).

[0043] The polymer was dispersed in a 95 / 5 DMSO / water solution kept at 5° C. until the concentration of polymer in the solvent was 17.5 wt %.

[0044] Dissolution of the polymer in the solvent solution was carried out on an industrial line for the production of spinning solutions of acrylic polymers. After heating the dispersion at 88 °C for 90 s using a tube bundle exchanger, a homogeneous dope with a viscosity of 350 poise at 60 °C was obtained.

[0045] The resulting solvent polymer solution was fed into a spinning line for carbon fiber precursors.

[0046] During the spinning process, the spinneret was immersed in a coagulation bath consisting of a mixture of water and DMSO, producing perfectly round, compact, crack-free fibers. The resulting fibers were washed with deionized water to remove residual solvent, stretched to approximately 10 times their original length by various passes through boiling water, dried on hot rollers, and collected on a reel. The resulting tow was composed of fibers with a diameter of approximately 12 microns, an average strength of 56 cN / Tex, and an ultimate elongation of approximately 17% measured in a 10 N cell using an Instron 5542 dynamometer according to ASTM D-3822.

[0047] The precursor tow thus obtained is treated in an oxidation furnace with a temperature gradient of 240-270 °C for 90 minutes, finally obtaining an oxidized fiber of PANOX type with a density of 1.39 g / cc. The oxidized fiber is then fed into a carbonization section with a maximum temperature of 1,600 °C, resulting in a carbon fiber with a tenacity equal to 4.60 GPa and an elastic modulus of 245 MPa. Example 2

[0048] Dissolution of high molecular weight acrylic copolymers (nMW=150,000-180,000) consisting of acrylonitrile (96% by weight relative to the total weight of the polymer), itaconic acid (1% by weight relative to the total weight of the polymer) and methyl methacrylate (3% by weight relative to the total weight of the polymer).

[0049] The polymer was converted into a dope in the same manner as described in Example 1, except that a mixture of DMSO (95 wt%) and 5 wt% of 1.5 wt% aqueous ammonia was used as the solvent medium, and the conversion was carried out until the polymer concentration in the solvent reached 17.5 wt%. A slurry was prepared at a temperature of 5°C, and then heated to 88°C for 90 seconds to obtain a homogeneous spinning dope with a viscosity of 380 poise at 60°C.

[0050] The resulting solvent polymer solution was then fed into a spinning line for carbon fiber precursors.

[0051] During the spinning process, the spinneret was immersed in a coagulation bath consisting of a mixture of water and DMSO, producing perfectly round, compact, crack-free fibers. The resulting fibers were washed with deionized water to remove residual solvent, stretched to approximately 10 times their original length by various passes through boiling water, dried on hot rollers, and collected on a reel. The resulting tow was composed of fibers with a diameter of approximately 12 microns, an average tenacity of 58 cN / Tex, and an ultimate elongation of approximately 18% measured in a 10 N cell using an Instron 5542 dynamometer according to ASTM D-3822.

[0052] The precursor tow thus obtained is treated in an oxidation furnace with a temperature gradient of 240-260 °C for 60 min, finally obtaining PANOX type oxidized fibers with a density of 1.43 g / cc. The oxidized fibers are then fed into a carbonization section with a maximum temperature of 1,600 °C, resulting in carbon fibers with a tenacity equal to 5.20 GPa and an elastic modulus of 288 MPa. Example 3

[0053] Dissolution of high molecular weight acrylic copolymers (nMW=180,000-200,000) consisting of acrylonitrile (97% by weight based on the total weight of the polymer) and itaconic acid (3% by weight based on the total weight of the polymer).

[0054] The polymer was converted into a dope in the same manner as described in Example 1, except that a mixture of DMSO (94 wt%) and 6 wt% of 3 wt% aqueous ammonia was used as the solvent medium, and the conversion was carried out until the polymer concentration in the solvent reached 17.5 wt%. A slurry was prepared at a temperature of 4°C, and a spinning dope was obtained by heating at 88°C for 90 seconds. A homogeneous dope with a viscosity of 450 poise at 60°C was obtained.

[0055] The resulting solvent polymer solution was then fed into a spinning line for carbon fiber precursors.

[0056] During the spinning process, the spinneret was immersed in a coagulation bath consisting of a mixture of water and DMSO, producing perfectly round, compact, crack-free fibers. The resulting fibers were washed with deionized water to remove residual solvent, stretched to approximately 10 times their original length by various passes through boiling water, dried on hot rollers, and collected on a reel. The resulting tow was composed of fibers with a diameter of approximately 12 microns, an average tenacity of 65 cN / Tex, and an ultimate elongation of approximately 16% measured in a 10 N cell using an Instron 5542 dynamometer according to ASTM D-3822.

[0057] The precursor tow thus obtained is treated in an oxidation furnace with a temperature gradient of 240-260 °C for 40 minutes, finally obtaining an oxidized fiber of PANOX type with a density of 1.40 g / cc. The oxidized fiber is then fed into a carbonization section with a maximum temperature of 1,600 °C, resulting in a carbon fiber with a tenacity equal to 5.34 GPa and an elastic modulus of 295 MPa. Example 4

[0058] Dissolution of high molecular weight acrylic copolymers (nMW=150,000-180,000) consisting of acrylonitrile (96% by weight based on the total weight of the polymer), itaconic acid (1% by weight based on the total weight of the polymer) and methyl acrylate (3% by weight based on the total weight of the polymer).

[0059] The polymer was converted into a dope as described in Example 1, except that a mixture of DMSO (95 wt%) and 5 wt% of 3.5 wt% aqueous methylamine was used as the solvent medium until the polymer concentration in the solvent reached 17.5 wt%. A slurry was prepared at a temperature of 5°C, and then heated to 88°C for 90 seconds to obtain a homogeneous spinning dope with a viscosity of 380 poise at 60°C.

[0060] The resulting solvent polymer solution was then fed into a spinning line for carbon fiber precursors.

[0061] During the spinning process, the spinneret was immersed in a coagulation bath consisting of a mixture of water and DMSO, producing perfectly round, compact, crack-free fibers. The resulting fibers were washed with deionized water to remove residual solvent, stretched to approximately 10 times their original length by various passes through boiling water, dried on hot rollers, and collected on a reel. The resulting tow was composed of fibers with a diameter of approximately 12 microns, an average tenacity of 61 cN / Tex, and an ultimate elongation of approximately 16% measured in a 10 N cell using an Instron 5542 dynamometer according to ASTM D-3822.

[0062] The precursor tow thus obtained is treated in an oxidation furnace with a temperature gradient of 240-260 °C for 60 min, finally obtaining an oxidized fiber of PANOX type with a density of 1.41 g / cc. The oxidized fiber is then fed into a carbonization section with a maximum temperature of 1,600 °C, resulting in a carbon fiber with a tenacity equal to 5.12 GPa and an elastic modulus of 278 MPa. The present disclosure also includes the following aspects. <1> A method for preparing a homogenous spinning solution for producing an acrylic fiber precursor (PAN) for carbon fiber, comprising the steps of: i) a powdered acrylonitrile copolymer, a solvent comprising a mixture containing DMSO in an amount ranging from 90 to 99% by weight, based on the total weight of the solvent, and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 1 to 10% by weight; By mixing at a temperature in the range of 5-10°C, Preferably, A powdered acrylonitrile copolymer is a solvent consisting of a mixture comprising DMSO in an amount ranging from 93 to 98% by weight, preferably from 93 to 96% by weight, based on the total weight of the solvent, and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 2 to 7% by weight, preferably from 4 to 7% by weight, By mixing at a temperature of 5°C, preparing a homogenous suspension; a preparation step, the mixing being carried out by spraying a stream of DMSO solvent / aqueous ammonia and / or primary or secondary amine onto the stream of deagglomerated premixed acrylonitrile copolymer powder for a period ranging from 5 to 30 minutes; ii) heating the homogenous suspension from step i) at a temperature ranging from 70 to 150° C. for a time ranging from 0.5 to 30 minutes until the copolymer is completely dissolved to form a homogenous solution; A preparation method comprising: <2> The aqueous solution of ammonia or a primary amine or a secondary amine contains 1 to 10% by weight, preferably 2 to 7% by weight, of a nitrogen-containing compound based on the total weight of the solution. <1> The method described above. <3> The solvent is a mixture containing DMSO and aqueous ammonia; <1> or <2> The method described above. <4> the primary amine is selected from methylamine, ethylamine and isopropylamine, and / or the secondary amine is selected from dimethylamine, diethylamine and diisopropylamine; <1> or <2> The method described above. <5> The copolymer is a high molecular weight copolymer in the range of 100,000 to 300,000 Da, consisting of acrylonitrile in an amount ranging from 90 to 99% by weight based on the total weight of the polymer and one or more comonomers in an amount ranging from 1 to 10% by weight based on the total weight of the polymer. <1> ~ <4> 2. The method according to claim 1 , <6> The comonomer is a vinyl molecule having one or more acid groups selected from acrylic acid, methacrylic acid, and itaconic acid, and is preferably itaconic acid. <5> The method described above. <7> The copolymer also includes a third comonomer selected from neutral vinyl molecules such as methyl acrylate, methyl methacrylate, vinyl acetate, acrylamide, etc. <1> ~ <6> 2. The method according to claim 1 , <8> <1> ~ <7> 2. A homogeneous spinning solution for the production of acrylic fiber precursors of carbon fibers, which can be obtained by using any one of the methods described in claim 1 to 11. <9> A method for producing carbon fibers, comprising the steps of: <1> ~ <7> The homogeneous solution obtained by any one of the above steps is iii) spinning the homogeneous solution obtained in step ii) to obtain a tow containing 500 (0.5K) to 400,000 (400K) single fibers, preferably 1,000 (1K) to 50,000 (50K) single fibers; iv) a flame retarding or oxidation step for the tow obtained in step iii), said oxidation being carried out at a temperature in the range of 240-260° C. for a time in the range of 40-120 minutes; v) subjecting the oxidized tow obtained in step iv) to a carbonization step at a maximum temperature of 1,600°C; Further methods of carrying out the above. <10> <9> Carbon fiber obtained by the method according to the above.

Claims

1. A method for preparing a homogenous spinning solution for producing an acrylic fiber precursor (PAN) for carbon fiber, comprising the steps of: i) a powdered acrylonitrile copolymer, a solvent comprising a mixture comprising DMSO in an amount ranging from 90 to 99% by weight, based on the total weight of the solvent, and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 1 to 10% by weight, By mixing at a temperature in the range of 5-10°C, preparing a homogenous suspension; a preparation step, said mixing being carried out for a period ranging from 5 to 30 minutes by spraying a stream of DMSO solvent / aqueous ammonia and / or primary or secondary amine onto the stream of deagglomerated premixed acrylonitrile copolymer powder; ii) heating the homogenous suspension from step i) at a temperature ranging from 70 to 150° C. for a time ranging from 0.5 to 30 minutes until the copolymer is completely dissolved to form a homogenous solution; A preparation method comprising:

2. 2. The method according to claim 1, wherein the aqueous solution of ammonia or a primary or secondary amine contains 1 to 10% by weight of a nitrogen-containing compound based on the total weight of the solution.

3. 3. The method of claim 1 or claim 2, wherein the solvent comprises a mixture comprising DMSO and aqueous ammonia.

4. 3. The method according to claim 1 or 2, wherein the primary amines are selected from methylamine, ethylamine and isopropylamine and / or the secondary amines are selected from dimethylamine, diethylamine and diisopropylamine.

5. 5. The method of any one of claims 1 to 4, wherein the copolymer is a high molecular weight copolymer in the range of 100,000 to 300,000 Da, consisting of acrylonitrile in an amount ranging from 90 to 99 wt.%, based on the total weight of the polymer, and one or more comonomers in an amount ranging from 1 to 10 wt.%, based on the total weight of the polymer.

6. The method of claim 5, wherein the comonomer is a vinyl molecule having one or more acid groups selected from acrylic acid, methacrylic acid, and itaconic acid.

7. 7. The method of any one of claims 1 to 6, wherein the copolymer also comprises a third comonomer selected from a neutral vinyl molecule selected from methyl acrylate, methyl methacrylate, vinyl acetate, acrylamide.

8. The method of claim 5, wherein the comonomer is itaconic acid.

9. A method for producing carbon fibers, comprising the steps of: iii) spinning the homogeneous solution from step ii) to obtain a tow containing 500 (0.5K) to 400,000 (400K) single fibers; iv) a flame retarding or oxidation step on the tow obtained in step iii), said oxidation being carried out at a temperature in the range of 240-260° C. and for a time in the range of 40-120 minutes; v) subjecting the oxidized tow obtained in step iv) to a carbonization step at a maximum temperature of 1,600° C.; Further methods of carrying out the above.

10. The method of claim 1, wherein in step i) the solvent consists of a mixture comprising DMSO in an amount ranging from 93 to 98% by weight, relative to the total weight of the solvent, and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 2 to 7% by weight, and the mixing is performed at a temperature of 5°C.

11. The method of claim 1, wherein in step i) the solvent consists of a mixture comprising DMSO in an amount ranging from 93 to 96% by weight, relative to the total weight of the solvent, and an aqueous solution of ammonia and / or one or more primary amines and / or one or more secondary amines in an amount ranging from 4 to 7% by weight, and the mixing is performed at a temperature of 5°C.

12. The method of claim 9, wherein in step (iii), a tow is obtained comprising between 1,000 (1K) and 50,000 (50K) single fibers.

Citation Information

Patent Citations

  • JP1973063029A

  • Production of carbon fiber tow

    JP1981049022A

  • Flame-resistant polymer and flame-resistant polymer solution

    JP2007031564A

  • Process for production of acrylic fibers

    JP2015132040A

  • Flame-resistant fiber, carbon fiber, and processes for the production of both

    WO2007018136A1